OPTIMIZATION OF LAMBLIASIS MICROSCOPIC DIAGNOSTICS BY THE METHOD OF POLARIZED FLUORESCENCE FOR PATIENTS WITH ROSACEA AND URTICARIAL - Maryana Kovalchuk; Mariia Shkilna; Mykhailo Andreychyn; Natalia Vasylieva; Vasyl Demyanenko (Our Dermatology Online, 2013)
Introduction: There is little information about diagnosis of concurrent lambliasis in patients with rosacea and urticaria. We used method of polarized fluorescence to diagnose liambliasis, taking into account belonging of macromolecular structures of unicellular parasites Giardia lamblia to the optically active substances with the properties of liquid crystals. Material and Methods: Lambliasis was diagnosed on the basis of feces parasitological research and duodenal contents by methods of light and optic microscopy and polarized fluorescence in 105 patients with rosacea and urticaria. Research results were processed by the method of variation statistics in the Statgraf program by using Student's criterion. Results: Search results of lamblia in patients with rosacea and urticaria depended on the conditions of its holding, patients' preparation and from the previously received basic therapy if it consisted absorbents. Due to the fact that the fluorescence polarization as a physical method does not require the use of any generally toxic, dye- fluorochromes, qualitative cyto fluorescent analysis of lamblia in greeting microdrugs enables to distinguish vegetative forms of cysts. Conclussions: Polarized fluorescence method allows optimize the microscopic diagnosis of lambliasis, increasing its sensitivity. Previous preparation for the laboratory examination of Giardia lamblia is needed for the best exposure of vermin for patients with rosacea and urticaria.